MOOC et Études Culturelles : que la créativité soit avec vous ! - Mélanie Bourdaa et Laurence Allard (Mise au Point)
This article exposes and analyzes two experiences of Mooc related to fan culture. The first one, « Understanding transmedia storytelling », led by Melanie Bourdaa for France Digital University, is devoted to these extensive narrative strategies in which the fans play a full part. The second one, entitled « Mooc of students » was led by Laurence Allard and part of a course on digital culture during which students designed 50 teaching modules following the logic of the overthrown class and situated knowledge.